Emotional intelligence in zakat institutions in Malaysia: a field study / Rozman Hj Md Yusof, Abd Hair Awang, Arifin Md Salleh, Mustafa Mohamad - Hj Md Yusof, Rozman; Awang, Abd Hair; Md Salleh, Arifin; Mohamad, Mustafa (Institute of Business Excellent (IBE), 2011)
This study explored the emotional intelligence dimensions (self-awareness, selfmanagement, social awareness and social skills) of employees employed in Zakat Centers. Data were collected from 113 randomly selected from three zakat centers: Melaka, Negeri Sembilan and Selangor using self-administered questionnaires of Emotional Competence Inventory (ECI) (108 items) that measured emotional intelligence. Overall, the study revealed that the employees’ emotional intelligence and its dimensions level: self-awareness, social-awareness and social skills are proficient, except for self-management, which was slightly low proficient.